Face masks have a limited influence on first impressions: evidence from three experiments. (June 2022) - C. Twele, Anita; M. Thierry, Sophia; J. Mondloch, Catherine
Considering the widespread use of face masks during the COVID-19 pandemic, the goal of the current study was to examine how occlusion of the lower half of the face may impact first impression formation. We conducted three experiments, each building on previous research, investigating the effect of face masks on first impressions of faces across the lifespan (children, young and older adults). Experiment 1 examined whether the mandatory influence of happy facial expressions on perceived trustworthiness in young adult faces is influenced by face masks. Experiment 2 examined behavioural consequences of adults' first impressions of child faces to determine whether masks reduce the effect of facial niceness on interpretations of ambiguous behaviour. Experiment 3 investigated consensus for first impressions of trustworthiness and competence in older adult faces with and without masks, as well as consensus on underlying facial cues. The results of all three experiments present converging evidence that masks do not have a significant impact on first impressions and their behavioural consequences.